Assessing the Economic Implications of a Diagnosis-Related Groups Payment System in Iran’s Health System Transformation Plan - Yousef Khadivi; Mohsen Nabi Meibodi; Fatemeh Saghafi; Reza Khadivi (International Journal of Preventive Medicine)
Background: The Health System Transformation Plan (HSTP) in Iran aimed to enhance universal health coverage through improved access and reduced out-of-pocket payments. However, rising healthcare expenditures have posed challenges. The Diagnosis-Related Groups (DRG) payment system has been implemented in developed countries to reduce costs, improve efficiency, and enhance service quality. This study estimates the potential cost savings in pharmaceutical and inpatient services within the HSTP framework, focusing on public hospitals affiliated with Isfahan University of Medical Sciences (MUI). Methods: This study was conducted in three stages. First, a cross-sectional study design was used to collect current inpatient and pharmaceutical costs from public hospitals affiliated with MUI before and after the health sector reform. Second, a meta-analysis was conducted to determine the effects of implementing the DRG payment system on the costs of inpatient and pharmaceutical services. Finally, the possible costs of medication and hospitalization in 2015 were estimated by applying the annual inflation rate. The predicted costs were calculated by multiplying the impact values of the DRG payment system on the estimated expenses in 2015. The potential cost savings were calculated by subtracting the current expenses from the predicted expenses based on the DRG payment system. Results: Based on the assumption ratio of changes following the implementation of the DRG payment system, the study estimated cost savings of $60,282,055 in both inpatient and pharmaceutical expenses. Conclusions: Implementing the DRG payment system could have resulted in significant cost savings, equivalent to 9.2% of the total health sector expenditures of MUI.